2016
DOI: 10.1071/cp15417
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging at tillering affects spike and spikelet formation in wheat

Abstract: Waterlogging stress is one of the limiting factors influencing wheat (Triticum aestivum L.) production. Wheat tolerance to waterlogging is related to the duration of the waterlogging event, the crop development stage in which waterlogging occurs, and the sensitivity of genotype. In this paper we investigated the impact of eight waterlogging durations (from 0 to 60 days) imposed at 3-leaf and 4-leaf growth stages (~30 and 40 days after sowing) on grain yield, grain yield components, straw and root dry weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 29 publications
2
46
3
Order By: Relevance
“…70%-80% of controls during tillering) (Herzog, Striker, Colmer, & Pedersen, 2016;de San Celedonio, Abeledo, & Miralles, 2014). Also, the effect of waterlogging on the components of yield differs between these two cereals: in wheat, waterlogging mostly reduces the grain number per spike (due to a lesser spikelet fertility), whereas in barley it constrains the number of spikes per plant (Arduini, Orlandi, Pampana, & Masoni, 2016;de San Celedonio et al, 2014). Similarly, waterlogging affects seed production differentially along the life cycle in rapeseed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70%-80% of controls during tillering) (Herzog, Striker, Colmer, & Pedersen, 2016;de San Celedonio, Abeledo, & Miralles, 2014). Also, the effect of waterlogging on the components of yield differs between these two cereals: in wheat, waterlogging mostly reduces the grain number per spike (due to a lesser spikelet fertility), whereas in barley it constrains the number of spikes per plant (Arduini, Orlandi, Pampana, & Masoni, 2016;de San Celedonio et al, 2014). Similarly, waterlogging affects seed production differentially along the life cycle in rapeseed.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, wheat would have better chances of producing an acceptable grain production with transient waterlogging of up to two weeks in either early or late plant stages; barley and rapeseed can generate acceptable yield if waterlogged early but are susceptible to yield loss if waterlogging occurs during the reproductive stage; and field pea is not suitable for areas prone to waterlogging. Lastly, it should be noted that genotypic variation for waterlogging tolerance can exist within each species (e.g Arduini et al, 2016, Collaku & Harrison, 2002Masoni et al, 2016, Pang et al, 2004. Xu et al, 2018 for rapeseed;…”
mentioning
confidence: 99%
“…GW, an important determinant of milling quality, was reduced by W treatments depending on S and Fusarium presence. Unlike, Arduini et al (2016) showed that the mean kernel weight in two wheat cultivars evaluated was not affected by waterlogging.…”
Section: Discussionmentioning
confidence: 83%
“…One of the most common abiotic stress factors that affects crops is waterlogging, which is responsible for losses representing 15-20% of the total area sown to wheat each year worldwide (Setter & Waters, 2003). This environmental event takes place when water excess saturates the soil by inadequate soil drainage or high rainfall resulting in anoxic and hypoxia within roots with consequences in the shoots (Arduini, Orlandi, Pampana, & Masoni, 2016;Herzog, Striker, Colmer, & Pedersen, 2016). Huang, Johnson, Nesmith, and Bridges (1994) evaluated several wheat genotypes under hypoxia and observed that the reduction of O2 enhances the aerenchyma formation in roots to improve the internal O2 diffusion in plants as a mechanism for hypoxia tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Dickin et al [10] considered that vigorous growth after waterlogging conducted at the seedling stage eliminated the damages and that the final yield was not negatively affected. However, it has also been suggested that a full recovery is not possible, due to a reduction in the establishment of large-spikes [25,26]. These results suggest that the degree of recovery after waterlogging profoundly affected the potential of yield loss.…”
Section: Introductionmentioning
confidence: 98%